The Influence of Digital Competence, Visionary Leadership, and Employee Creativity on Performance of Apparatus in the Department of Tourism and Creative Economy of Lampung Province - Romi Amelia; Febrianty; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the effect of digital competence and visionary leadership on apparatus performance with employee creativity as a mediating variable at the Department of Tourism and Creative Economy of Lampung Province. The background of this research is based on the demands of digital transformation and leadership strengthening in the public sector, which require civil servants to possess digital capabilities, visionary leadership, and creativity to enhance organizational performance. This study employs a quantitative approach using a survey method through the distribution of questionnaires to employees at the Department of Tourism and Creative Economy of Lampung Province. Data were analyzed using Structural Equation Modeling (SEM) to examine both direct and indirect relationships among the research variables. The results indicate that digital competence has a positive and significant effect on apparatus performance and employee creativity. Employee creativity also has a positive and significant effect on apparatus performance. Meanwhile, visionary leadership has a positive but insignificant effect on employee creativity. Furthermore, employee creativity is prosven to mediate the relationship between digital competence and apparatus performance, but does not significantly mediate the relationship between visionary leadership and apparatus performance. These findings confirm that strengthening digital competence and employee creativity is a key factor in improving apparatus performance at the Department of Tourism and Creative Economy of Lampung Province.